CHEMICAL FINGERPRINT AND BIOACTIVITIES OF SOLANUM NIGRUM L. AND SOLANUM MELONGENA L. - A COMPARATIVE ASSESSMENT OF TWO SOLANACEAE SPECIES - ATIYA BATOOL; ajwa; SAADIYA ZIA; iqra saleem; FATMA HUSSAIN (Kashmir Journal of Science, 2025)
Medicinal plants have a vital role in health and beyond traditional medications; these are part of modern pharmaceutical landscape. The present study was designed to compare and contrast phytochemistry and bioactivities of Solanum nigrum (SN) and Solanum melongena (SM); two species of Solanaceae family. Aqueous leaf extracts were used to assess total phenolic contents (TPC) and total flavonoid contents (TFC), free radical scavenging activity, alpha amylase inhibition (antidiabetic activity), antimicrobial and cytotoxic activities along with chemical fingerprint by Fourier transform infrared spectroscopy (FTIR). TPC in SN and SM extracts were 32.73 ± 2.08 mg GAE/100g and 43.98 ± 0.12 mg GAE/100g respectively. TFC of SN extract was 69.69± 0.538mg CE/100g and TFC of SM was 89.545± 0.19mg CE/100g.  SN and SM extracts showed 70.52 ± 0.73 % and 74.13 ± 0.60 % free radical scavenging capacity respectively. In antimicrobial assay, SN showed antimicrobial activity against E. coli with 9mm area of growth inhibition and 12 mm inhibition zone was observed against S. aureus. Meanwhile, SM showed 9 mm of inhibition zone against E.coli as well as 9.3mm of inhibition zone against S. aureus, which indicates the presence of antimicrobial potential. SN and SM exhibited 28.64±3.22% and 28.2±2.21% inhibition of amylase enzyme. Aqueous extract of Solanum nigrum showed 10.76% hemolytic activity, aqueous extract of Solanum melongena showed 5.27% hemolytic activity and positive control had 94.87% hemolytic activity. FTIR spectra confirmed the presence of diverse secondary metabolites. Both species of Solanaceae family exhibited analogous anti-diabetic and anti-microbial activities. However, S. melongena was slightly less toxic as compared to Solanum nigrum. These are preliminary assessments that have contributed to the existing data but in real-world scenario, animal trials can better fabricate their application in medicine.